Phthalocyanine and Its Formulations: A Promising Photosensitizer for Cervical Cancer Phototherapy - Lucimara R. Carobeli; Lyvia E. de F. Meirelles; Gabrielle M. Z. F. Damke; Edilson Damke; Maria V. F. de Souza; Natália L. Mari; Kayane H. Mashiba; Cristiane S. Shinobu-Mesquita; Raquel P. Souza; Vânia R. S. da Silva; Renato S. Gonçalves; Wilker Caetano; et al. (MDPI AG, 2021)
Cervical cancer is one of the most common causes of cancer-related deaths in women worldwide. Despite advances in current therapies, women with advanced or recurrent disease present poor prognosis. Photodynamic therapy (PDT) has emerged as an effective therapeutic alternative to treat oncological diseases such as cervical cancer. Phthalocyanines (Pcs) are considered good photosensitizers (PS) for PDT, although most of them present high levels of aggregation and are lipophilic. Despite many investigations and encouraging results, Pcs have not been approved as PS for PDT of invasive cervical cancer yet. This review presents an overview on the pathophysiology of cervical cancer and summarizes the most recent developments on the physicochemical properties of Pcs and biological results obtained both in vitro in tumor-bearing mice and in clinical tests reported in the last five years. Current evidence indicates that Pcs have potential as pharmaceutical agents for anti-cervical cancer therapy. The authors firmly believe that Pc-based formulations could emerge as a privileged scaffold for the establishment of lead compounds for PDT against different types of cervical cancer.